Prefontal cognitive ability, intelligence, big five personality and the prediction of advanced academic and workplace performance . [article]. - Higgins, Daniel M.
Study 1 and 2 assessed performance of a battery of dorsolateral prefontal cognitive ability (D-PFCA) tests, personality, psychometric intelligence, and academic performance (AP) in 2 i=undergraduate samples. iIn studies 1 and 2, AP was correlated with D-PFCA (r=.37, p<.01, and r-.33, p<.01,respectively), IQ (r=.24, p<.05, and r=.38, p<01, respectively). and conscientiousness (r=.26, p<.05, and r=.37, p<.01, respectively). D-PFCA remained significant in regression analyses controlling for intelligence (or g) and personality. Studies 3 and 4 assessed P-PFCA, personality and workplace performance among (a)managerial-administrative workers and (b)factory floor workers at a manufacturing company. Prefontal cognitive ability correlated with supervisor ratings of manager performance at values of r ranging from .42 to .57 (ps<.001), depending on experience, and with factory floor performance at pr=.21 (p=.02), after controlling for experience, age, and education. Conscientiousness correlated with factory floor performance at r=.23.